Research of the Rheological Modification Mechanism of Crumb Rubber-Modified Asphalt Containing Polyamide 6 Additive - Zhihua Tan; Jijing Wang (Advances in Civil Engineering)
In the past few decades, the rapid growth of automobile production in China has led to the scrapping of a large number of tires. How to dispose of tires has become a significant challenge. The addition of crushed rubber to asphalt binder not only can improve the performance of asphalt mixtures but also is an effective and environmentally friendly way to recycle scrapped tires. However, rubber asphalt mixtures demand higher production temperatures than conventional asphalt binders due to the higher viscosity of asphalt rubber binder. The main objective of this study is to evaluate the rheological properties of rubber-modified asphalt by adding polyamide 6 and investigate the modification mechanism of crumb rubber-modified asphalt (CRMA) after adding polyamide 6. To this end, the content of waste rubber in the prepared rubber asphalt was 20%. The conventional laboratory rheological tests were employed to evaluate the performance of crumb rubber-modified asphalt after adding polyamide 6. Furthermore, to investigate the interaction mechanism of crumb rubber and asphalt, a series of advanced tools, including the scanning electron microscopy (SEM) test, differential scanning calorimeter (DSC) test, and Fourier transform infrared spectroscopy (FTIR) test, were conducted. From the experimental results obtained, it may be concluded that crumb rubber-modified asphalt with adding polyamide 6 not only improves the engineering properties of the rubber-modified asphalt but also improves the performance of rubber asphalt. From the FTIR and SEM tests, it is concluded that there is no new functional group in the mixing process of crumb rubber and the asphalt, which contributes to the storage stability of asphalt binder and runway.